慢性腹膜透析患者の腹部大動脈瘤に対する分岐型人工血管置換術 - 高江, 久仁; 小櫃, 由樹生; 重松, 宏; 槇村, 進; 飯田, 泰功; 佐藤, 正宏; 佐藤, 和弘; 佐伯, 直純; 小泉, 信達 (Japanese Journal of Vascular Surgery, 2008)
A 59-year-old man was admitted for repair of an infrarenal abdominal aortic aneurysm. He had also been receiving continuous ambulatory peritoneal dialysis (CAPD). We performed hemodialysis using a double-lumen catheter from 7 days before the operation, and bifurcated grafting was accomplished through the right retroperitoneal approach. Hemodialysis was continued for 3 weeks postoperatively, and then returned to CAPD. He was discharged 34 days after the operation without any decrease in his activities of daily life. This is apparently the first case of repair for abdominal aortic aneurysm associated with CAPD in Japan. 症例は59歳男性．2006年 9 月，慢性腎不全にて他院にてCAPD導入．精査中にCTにて最大短径58mmの腎動脈下腹部大動脈瘤を指摘され，手術目的に当院紹介入院．術前より血液透析に切り替え，右後腹膜アプローチにて分岐型人工血管置換術を施行した．術後 3 週間はCAPDに加え血液透析を併施し，徐々に腹膜透析に移行し第34病日に退院となった．術式の選択と術後管理につき文献的考察を加え報告する．